‘There’s no functioning child panel in this region’: an assessment of child panels in Ghana’s juvenile justice system - Ame, Robert Kwame (Contemporary justice review, 2020)
Child Panels (CPs) are quasi-judicial bodies charged with administering alternative measures in accordance with the Juvenile Justice Act and the Children’s Act in Ghana. This study set out to examine the functioning, relevance, efficiency, and sustainability of CPs. Drawing on qualitative research methods of observation, semi-structured interviews, and a case study, the major findings of this study include a lack of awareness of the concept and existence of CPs with only one functioning CP in 12 districts in the study area that were supposed to have them, and a general lack of training for members of the panel. Notwithstanding these findings, when researchers prodded, interviewees’ responses pointed to tremendous support for the concept of CPs. The paper argues that implemented well, CPs have the potential to enhance access to justice for all children in the country considering their composition and requirement that they be formed by every municipal and district assembly in the country, which makes them more accessible to parents and their children everywhere in the country than other state agencies within the juvenile justice system. Hence, the paper recommends that CPs should be equipped to function efficiently.